VD_FINDINFO AI 127/09 - 351/2012 vom 29. Oktober 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, DEGRÉ DE L'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, ENQUÊTEEN GÉNÉRAL | 17 al. 1 LAI, 28 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA